PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN MELALUI PELATIHAN PADA PERUSAHAAN AIR MINUM TIRTA MANGKALUKU KOTA PALOPO - Salju (MANAJEMEN DEWANTARA, 2023)
This study aims to determine how training variables can affect employee productivity. The respondents in this study were 76 employees of the Tirta Mangkaluku Drinking Water Company. Data collection was carried out using the observation, interview and questionnaire methods, the data analysis method used was simple linear regression analysis using IBM (SPPS) V.24 assistance and hypothesis testing using the t test, the results of the Simple Linear Regression Analysis showed that Training affects Productivity Employee 0.835 means, if the training variable increases by 0.835 then employee productivity will increase linearly by 0.835, while the results of the t test research show that the independent variable namely Training (X) partially has a significant effect on Employee Productivity (Y), seen from the calculation t test obtained t-count 13.672 > t-table 1.66600. The implication of this research is the importance of companies providing training to improve the quality and competitiveness of their employees so that their productivity is maintained